Exploring the ethical decision-making experience of caregivers of end stage cancer patients in Iran: a phenomenological study - Seyedeh Esmat Hosseini; Alireza Nikbakht Narabadi; Ali Abbasi; Soodabe Joolaee; Neda Sheikhzakaryaee; Mahboobeh Shali (BMC Medical Ethics)
Abstract Background Ethical decision making is a complex issue because it strongly depends on the religion, beliefs, traditional laws and moral views of each society. The purpose of this study was to explore the experience of Iranian family caregivers of end stage cancer patients about ethical decision making. Methods This qualitative study is based on van Manen’s method of hermeneutic phenomenology. In-depth interviews were carried out to collect data. Participants were 12 caregiver. Audiotapes were transcribed and analyzed for common themes that represented the participants’ experiences. Trustworthiness of the findings was established using the Lincoln and Guba’s criteria. Results Three themes reflected the essence of caregivers’ lived experience including; fluctuating between hope and despair, wandering dilemma, and ethical decision making. Each of these themes consisted of several subthemes. Conclusion The present study revealed that, the caregivers of terminally ill cancer patients need different information about prognosis and end of life decision making process. Our perception of how families negotiate ethical issues in their decision-making is still developing. Opportunities should be created to empowering caregivers to talk about their uncertainties and concerns.